Student Teachers Perceptions and Experiences on School Practice and Competence Development at Makerere University-Uganda - Bwiruka, Jane; Maani, John; Ssetumba, John (American Journal of Education and Practice, 2021)
Purpose: The study was carried out to explore the student teachers' perceptions and experiences on school practice in terms of competence development. Methodology: Phenomenology as a design was adopted using unstructured interviews and documents review to collect data from twelve purposively selected third year student teachers as participants. Data was analyzed using the framework analysis. Findings: School practice was clearly understood by participants as a learning experience that involves putting theory into practice with the help from supervisors and senior teachers. However, it was conducted along the curriculum requirements as an assessment/examination by the university supervisors. Consequently, some challenges were faced. These included, difficulties in applying all the various methods taught by different lecturers, lack of professionalism, little feedback/conferencing with supervisors, hurried reports, limited mentorship and supervisory aspects in school practice host schools and limited materials to use among others. Unique Contribution to Theory, Practice and Policy: The teacher preparation institutions in Uganda Makerere inclusive need to improve the general methods course to all students to cater for issues in lesson preparation, presentation, classroom management, assessment and evaluation. An interdependent relationship between the University and the SP host schools is required to promote a working relationship between the supervisors and host teachers for mentoring and supervisory aspects to student teachers. Makerere University and other teacher preparation institutions need constant professional development courses to promote professionalism among supervisors to address issues like lack of feedback/conferencing and poor supervisor-student relationships among others.